Poemas em Língua Brasileira de Sinais : uma proposta de análise formal - Ribeiro, Nayara Piovesan (2016)
Over the years, research and studies about the Brazilian Sign Language – Libras - have gained great prominence within the academic community in Brazil. Despite all the efforts and dedication of researchers and scholars in the field, little is known about the linguistic structures about that language if we consider that the academic studies in this area are relatively recent. We know that this interest is still restricted to a small community of scholars and researchers almost exclusively made up of those who in one way or another are in contact with the deaf community and with users of the language. Libras, like any other language, is composed of a complex system of linguistic structures which allow users to communicate and express themselves artistically. Therefore, aimed at valuing Libras as a language of culture which conveys aesthetic manifestations, the research herein presented seeks to identify constituents of poems in Libras through formalist and stylistic analysis, in order to consolidate and advance the preliminary research findings in this area, such as those by Klamt (2014) and Machado (2013). To highlight the features of the poems in Libras, we selected four poems by Brazilian deaf poets, produced exclusively in Libras: "Cinco sentidos" (2009) and "Luz sem fim" (2011), by Nelson Pimenta; "Mãos do mar" (2011), by Alan Henry; and "Mãos iguais" (2011), by Wilson Santos Silva. To analyze these video productions, we used the ELAN software, which enabled the identification and analysis of aesthetic effects inherent to these poems. Through the analysis it was possible to identify some formal elements of the deaf poems although it has repeatedly been necessary to resort to comparisons with poems in oral languages, since we needed a starting point in Literary Theory to approach the process of poetic creation in Libras. As a result of this research, it was possible to identify markers of rhythm and rhyme in the deaf poems analyzed. It is also expected, as a development of this research, to discover new unique poetic features of sign languages, so that it is reaffirmed as an independent language from oral languages, including its aesthetic manifestations.